Technical Efficiency of Indonesia's Education Sector Before and During the COVID-19 Pandemic: A Data Envelopment Analysis (DEA) Application - Aliyuddin, Muhammad; Surgawati, Iis; Supriadi, Apip (Terbuka Journal of Economics and Business, 2024)
The education sector is one of the areas impacted by the COVID-19 pandemic. Nevertheless, its management must continue to be implemented well and efficiently. The aim of this study is to examine the technical efficiency of the education field in Indonesia before and during the COVID-19 pandemic. The research period spans 4 years, from 2018 to 2021. This study focuses on the 33 provinces in Indonesia. The data analysis technique used is non-parametric efficiency analysis using Data Envelopment Analysis (DEA), and assumes Variable Return to Scale (VRS) and is output-oriented. Estimation results indicate that the majority of provinces (81%) experienced a decline in average efficiency scores during the pandemic. All of these provinces are located outside of Java Island. Furthermore, there are provinces that saw an increase in efficiency scores during the pandemic, namely East Java, Central Java, Lampung, Jambi, West Papua, and Yogyakarta. Meanwhile, provinces that did not experience a change in average efficiency scores before and during the pandemic are Riau, Jakarta, West Java, Banten, Bali, North Kalimantan, and Gorontalo